Effects of graft modification on mechanical properties of epoxy resin - Teh, Letitia Kai Yue (Nanyang Technological University, 2024)
Epoxy resin is widely used as electrical insulation material due to its excellent combination of properties that make it ideal for various applications in the electrical and electronics industries. It is known for its high dielectric strength, good adhesion, and good chemical resistance. Other properties such as thermal stability, good mechanical strength versatility are also characteristic of epoxy resin, making it an ideal choice of materials for electrical insulator. Additive are commonly used to enhance their properties.